(untitled) (The Strategic Review for Southern Africa, 2020)
South Africa has often been lauded as an influential and pivotal actor inpeace and security affairs on the evolving African peace and security architecture. The centrality of Africa in South Africa's foreign policy has driven its exercise of peace diplomacy in a significant number of conflicts in Africa; where its mode of engagement has ranged from mediation to peacekeeping and post-conflict reconstruction and development assistance. Concomitant to its peace actor profile, South Africa's repertoire as an emerging development partner also forms a large part of its African agenda. The embedding of sustainable peace as a goal in the post2015 development agenda and the enduring relevance of the securitydevelopment nexus continue to exert profound influence on the parameters and conduct of South Africa's foreign policy and its pointedly Afro-centric agenda. This article argues for greater integration and harmonisation between South Africa's peace diplomacy and its development partnership agenda through the formulation of a peacebuilding and stabilisation strategy.